2017
DOI: 10.1039/c7ra04236a
|View full text |Cite
|
Sign up to set email alerts
|

The normal stress of an electrorheological fluid in compression mode

Abstract: This work studied the normal stress of an ER fluid in compression mode through both experiment and simulation. The TiO 2 based ER fluid was used to test the normal stress under different DC voltages and compressive speeds. The normal stress reached about tens of kPa and was affected by the applied voltage and compressive parameters. Then, a simulation model was presented to investigate the influencing factors on the normal stress. The computational normal stresses agreed well with the experimental results. Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The electrostatic interaction is responsible for the maintenance of the ER chain structure and hinders the flow, whereas the hydrodynamic interaction forces tend to destroy the chain structure and enhance the flow. Hence, the high and stable shear stress of W-TTO ER fluids further confirms that W-TTO particles possess not only large polarizability but also the fast response time to keep the structures and rheological properties stable. Comparing the flow curves of TTO ER fluids with those of W-TTO ER fluids (Figures S8, S10, and a,c), it is observed that the shear stresses of both low-concentration (19%) ER fluids remain stable during the entire shear rate range under different electric field strengths. When the concentration increases to 32%, the shear stress of W-TTO ER fluids still maintains a stable level but for TTO ER fluids, the shear stress reaches a maximum value and then decreases rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…The electrostatic interaction is responsible for the maintenance of the ER chain structure and hinders the flow, whereas the hydrodynamic interaction forces tend to destroy the chain structure and enhance the flow. Hence, the high and stable shear stress of W-TTO ER fluids further confirms that W-TTO particles possess not only large polarizability but also the fast response time to keep the structures and rheological properties stable. Comparing the flow curves of TTO ER fluids with those of W-TTO ER fluids (Figures S8, S10, and a,c), it is observed that the shear stresses of both low-concentration (19%) ER fluids remain stable during the entire shear rate range under different electric field strengths. When the concentration increases to 32%, the shear stress of W-TTO ER fluids still maintains a stable level but for TTO ER fluids, the shear stress reaches a maximum value and then decreases rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…For example, smart uids responding to electric elds (EFs), are formed by electricallypolarizable particles dispersed in a non-conducting liquid medium, [40][41][42][43] and may be utilized in dampers, valves, engine mounts, hydraulic actuators, squeeze mounts, medicine (e.g., in drug delivery or haptic medical devices), and food processing. [44][45][46][47] The industrial applications of currently known electrorheological (ER) uids are based on a positive ER effect, 44,47,48 resulting from the EF-controlled orientation of dispersed particles (e.g., metal oxides, 41,42 metal salts, 43 and modied polymeric particles 40 ) into chain-like structures accompanied by a transition of uid from liquid to viscoelastic system. However, there are many applications in which a controllable decrease in viscosity would be desirable (e.g., hydrostatic journal bearing for controlling rotor vibrations or squeeze lm damper for actively controlling rotor dynamics).…”
Section: Introductionmentioning
confidence: 99%
“…This technique can effectively predict the force-displacement and force-velocity curves with high accuracy. Wang et al [30] assumed that the number of ERF particles was constant during the squeeze process and obtained the normal stress according to the particle motion equation and particle interaction relationship. They investigated the effect of shear rate on the normal stress during compression.…”
Section: Introductionmentioning
confidence: 99%